1993
DOI: 10.1111/j.1600-0676.1993.tb00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of serum 2‘,5’‐oligoadenylate synthetase activity during interferon treatment of chronic hepatitis C

Abstract: ABSTRACT— It was our aim to evaluate whether the baseline activity of 2–5 oligoadenylate synthetase (2–5 OAS) in serum and changes induced by the treatment with interferon are relevant factors in remission of chronic hepatitis C. Seventeen out of 30 adult patients with chronic hepatitis C were randomized to receive recombinant alpha‐2b interferon at the dosage of 3 MU three times weekly. By the end of the third month, nine patients had normalized transaminase levels and continued to receive 3 MU of interferon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
6
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 23 publications
(6 reference statements)
3
6
1
Order By: Relevance
“…The median baseline OAS-1 plasma concentration of 580 pM observed in the present study is similar to that in a previous literature report (48). While the significant variability observed in placebo-treated patients over a 2-week period makes it difficult to gauge any danoprevir-related effects on OAS-1 concentration, the variability and lack of discernible correlation with antiviral response may have significant implications for the potential use of OAS-1 as a marker of response to treatment with interferon-free direct-acting antiviral regimens.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The median baseline OAS-1 plasma concentration of 580 pM observed in the present study is similar to that in a previous literature report (48). While the significant variability observed in placebo-treated patients over a 2-week period makes it difficult to gauge any danoprevir-related effects on OAS-1 concentration, the variability and lack of discernible correlation with antiviral response may have significant implications for the potential use of OAS-1 as a marker of response to treatment with interferon-free direct-acting antiviral regimens.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have reported increased OAS-1 expression during chronic HCV infection (26,38,48). Similar to the case with IP-10 (3,5,8,9,27), the baseline OAS-1 concentration is higher in nonresponders (NRs) to SOC treatment than in those that achieve SVR (48).…”
supporting
confidence: 48%
See 3 more Smart Citations